Evaluation of Different Desiccants for Groundnut (Arachis hypogaea) Pod Storage - R JERLIN; V VAKESWARAN; A ELAKIYA (Seed Research, 2024)
Drying of seeds plays a major role in extending the storability of seeds especially for oilseeds. Drying of Rabi harvested Groundnut pods is a very big challenge for the Groundnut farmers, because the pods are exposed to very hot sun, which leads to cracking of seed coat that will cause poor germination. Hence, to avoid exposing the groundnut pods to very high temperature, proper seed drying method is to be standardized. The desiccants are used to reduce the moisture content of the pods and seeds under laboratory conditions. Since various desiccants are available, suitable one with concentration has to be standardized foe extending the groundnut pod storability. Laboratory experiments were conducted to study the effect of different desiccants viz., anhydrous calcium chloride (14g/kg), silica gel (8.5g/kg) and zeolite beads (300g/kg) on the storability of groundnut pods cv. VRI 8 when stored in poly lined gunny bag under ambient condition .The result revealed that the performance of stored pods was decreased with advancement in storage period. Among all the treatments, storage of pods with zeolite beads (300g/kg) was found to be superior in maintaining low moisture content of 6.24% after six months of storage followed by silica gel (8.5g/kg) and anhydrous calcium chloride (14g/kg). The pods stored with zeolite beads (300g/kg) recorded higher germination per cent (78 per cent) and vigour index (2480), whereas lower values were recorded in lipid peroxidase activity (0.743 OD), electrical conductivity of seed leachate (0.174 dS/ m), insect infestation (8 per cent) and pathogen infection (5 per cent) after six months of storage. Hence, storage of groundnut pods with zeolite beads (300g/kg) can be practised to extend the storability of groundnut pods with minimum deterioration in seed quality.